HUBUNGAN ANTARA GANGGUAN PEMUSATAN PERHATIAN DAN HIPERAKTIVITAS DENGAN PRESTASI BELAJAR SISWA SDN 2 DAN SDN 3 BERKOH PURWOKERTO - Darmawan, Anton Budi; Hidayani, Ferra Nurul; Budi Setyaningsih, Tri Rini; Paramita, Hilma (MANDALA of Health, 2013)
Attention deficit/hyperactivity disorder (ADHD) is characterized by a pattern of diminished sustained attention (inattention), hyperactivity and higher levels of impulsivity in a child or adolescent than expected for someone of that age and developmental level. A child with ADHD usually gets a difficulty in learning process that cause the decreasing of achievement at school. The objective of this study was to know the correlation between ADHD with the achievement among students of SDN 2 and SDN 3 Berkoh Purwokerto. The method of this study was analytic observational with cross-sectional design studies and sampling techniques were purposive sampling and simple random sampling in 43 students; 19 students that had high risk of ADHD and 24 students without ADHD. Univariate analysis used table of frequency and bivariate analysis used chi square. Proportion of ADHD was 44,2%. There was a correlation between ADHD with the achievement (p=0,004; r=0,450). This result showed that there was a statistically significant correlation between ADHD with the achievement among students of SDN 2 and SDN 3 Berkoh Purwokerto